Micro and Nanoelectronics Devices, Circuits and Systems Select Proceedings of MNDCS 2021 - Lenka, Trupti Ranjan; Misra, Durgamadhab; Biswas, Arindam; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The book presents select proceedings of the International Conference on Micro and Nanoelectronics Devices, Circuits and Systems (MNDCS-2021). The volume includes cutting-edge research papers in the emerging fields of micro and nanoelectronics devices, circuits, and systems from experts working in these fields over the last decade. The book is a unique collection of chapters from different areas with a common theme and will be immensely useful to academic researchers and practitioners in the industry who work in this field.
Exploiting RF MEMS Switches for pattern reconfigurable parasitic antennas -- Comparative Analysis of Two-Stage Miller Compensated OPAMP in Bulk CMOS and FinFET Technology -- Performance-based Comparative Study on Single and Dual-Gate OTFT: Modeling and Simulation using TCAD -- Structural and Morphological Properties of Indium Doped Titanium Di-oxide Nanoparticles Synthesized Using Sol-gel Process -- Review of Emerging Tunnel FET Structures.
Keywords: Electronic circuits; Electronics; Microtechnology; Microelectromechanical systems; Mechanical engineering; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation; Microsystems and MEMS; Mechanical Engineering; Microelectronics -- Congresses; Nanoelectronics -- Congresses